An atypical presentation of a multiloculated giant pseudocyst of pancreas - Saxena, Pradeep; Lalchandani, Ankit; Sutrave, Tarun; Bhardwaj, Swastik (International Surgery Journal, 2021)
Giant pseudocysts of the pancreas are rare and difficult to manage. Pseudocysts are usually treated by cystogastrostomy but dependent drainage for giant pseudocysts may require alternative methods like cystojejunostomy. We report here a rare case of a multiloculated giant pseudocyst of pancreas which presented atypically with protrusion through the lesser omentum. The pseudocyst protruding through the lesser omentum filled the whole upper abdomen up to umbilical region and displaced the stomach inferiorly. The stomach which is usually displaced anteriorly by pseudocysts was unusually displaced and splayed on the inferior aspect of the pseudocyst. The anterior wall of the fundus and body of the stomach was adherent to the inferior aspect of the pseudocyst. The pseudocyst was managed by draining into the stomach in a different way by performing a cystogastrostomy to the anterior wall of the stomach. Giant pseudocysts are difficult to manage, and good imaging studies are helpful in selecting surgical options for dependent drainage. Cystogastrostomy on the anterior wall of the stomach is a feasible option to drain pseudocysts which are predominantly overlying and adherent to the anterior wall of the stomach.